2017
DOI: 10.3892/ol.2017.6034
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition in cancer: Role of the IL-8/IL-8R axis

Abstract: Abstract. Epithelial-mesenchymal transition (EMT) is a biological process that is associated with cancer metastasis and invasion. In cancer, EMT promotes cell motility, invasion and distant metastasis. Interleukin (IL)-8 is highly expressed in tumors and may induce EMT. The IL-8/IL-8R axis has a vital role in EMT in carcinoma, which is regulated by several signaling pathways, including the transforming growth factor β-spleen associated tyrosine kinase/Src-AKT/extracellular signal-regulated kinase, p38/Jun N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 114 publications
(138 reference statements)
0
24
0
Order By: Relevance
“…Moreover, IL-8 is an established factor that drives epithelial to mesenchymal transition in cancer cells ( 93 ). In the literature, there is a strong correlation between high expression of IL-8 and mesenchymal and stem cell features in tumor cells known for their aggressive behavior ( 94 , 95 ). Furthermore, treatment with conditioned media from cells secreting high levels of IL-8 induces epithelial-mesenchymal transition (EMT) in naive cells, while on the other hand, application of an IL-8 inhibitor leads to loss of mesenchymal markers and development of an epithelial phenotype ( 93 ).…”
Section: Non-cell Autonomous Contributions Of the Sasp To Senescencementioning
confidence: 99%
“…Moreover, IL-8 is an established factor that drives epithelial to mesenchymal transition in cancer cells ( 93 ). In the literature, there is a strong correlation between high expression of IL-8 and mesenchymal and stem cell features in tumor cells known for their aggressive behavior ( 94 , 95 ). Furthermore, treatment with conditioned media from cells secreting high levels of IL-8 induces epithelial-mesenchymal transition (EMT) in naive cells, while on the other hand, application of an IL-8 inhibitor leads to loss of mesenchymal markers and development of an epithelial phenotype ( 93 ).…”
Section: Non-cell Autonomous Contributions Of the Sasp To Senescencementioning
confidence: 99%
“…We found that only IL‐8 was positively correlated with weight loss in cachectic patients ( P = 0.044; r = 0.627), and this cytokine was also associated with the tumour size ( P = 0.006; r = 0.760). The literature demonstrated that enhanced expression of IL‐8 is associated with cachexia progression in pancreatic cancer and with induction of fibrosis in several types of tumours …”
Section: Resultsmentioning
confidence: 99%
“…The literature demonstrated that enhanced expression of IL-8 is associated with cachexia progression in pancreatic cancer 42 and with induction of fibrosis in several types of tumours. 36,43…”
Section: Inflammatory Cytokines and Growth Factors May Contribute To mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that when treating bladder cancer patients with BCG, parallel protective machineries are activated that could hinder the cancer eradication process and explain why some patients fail to respond to BCG. One such parallel process might be the secretion of IL‐8, which can act as a tumorigenic and pro‐angiogenic factor, driving tumor growth (Singh and Lokeshwar, ; Xie, ; Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 97%